SISTEM INFORMASI TERINTEGRASI ALAT TULIS KANTOR PADA BANK INTERNASIONAL INDONESIA CABANG LAMPUNG - nugroho, handoyo widi (IIB Darmajaya, 2011)
The organization sustainability at banking industry is a good coordinate and relationship between all units around there. One of them is availability office writing tools which request to support their work. Office writing tools need quickly available from storage unit to distribute automatically to all unit around it. Integration system absolutely needs to improve the later system that cannot support availability office writing tools so quickly. The later system done by manual system that fills a blank form request then gives to the storage unit. Storage unit will check availability office writing tools that their request then gives back to the unit who request. This process have done to all unit who request office writing tools, so it can be make a long time needed that can be bad influence of working performance at this organization. Case study is taken at Indonesian International Bank. Keywords: Information System, Integration, Office Writing Tools